UPAYA KONSELING KELOMPOK ISLAMI DALAM MENGATASI PERILAKU MENYIMPANG PADA MAHASISWA DI PERGURUAN TINGGI ISLAM - Pandy Akbar Wirawan; Beni Azwar; Dina Hajja Ristianti; Dewi Purnama Sari; Aida Rahmi Nasution (Jurnal Psikotes, 2025)
This study aims to describe the efforts of Islamic group counseling in addressing deviant behavior among students at the Faculty of Ushuluddin, Adab, and Dakwah (FUAD) IAIN Curup. Islamic group counseling is a guidance approach that combines modern counseling techniques with Islamic teachings, such as reciting verses from the Qur'an, praying together, dhikr, and reflective discussions. The research method used a qualitative case study approach with observation, in-depth interviews, and documentation techniques. The research findings indicate that Islamic group counseling effectively helps students recognize the negative impacts of deviant behavior, enhance religious awareness, strengthen self-control, and build commitment to change. The counseling process is implemented through stages of planning, group formation, counseling sessions, and periodic evaluations. Although proven to have positive impacts, the program faces challenges such as a shortage of competent counselors and insufficient supporting facilities. Therefore, institutional support and collaboration with student organizations are needed to ensure that Islamic group counseling can be implemented sustainably as a holistic and contextual model for student character development.